Validity and Reliability Analysis of a Problem-Based Learning Model with a Multimodal Approach - Gunawan, Gunawan; Kosim, Kosim; Qothrunnada, Qothrunnada; Zainuri, Baiq Nabila Saufika (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This research aims to develop and evaluate the validity and reliability of Problem-Based Learning (PBL) based learning materials with a multimodal approach to improve critical thinking skills and digital literacy of junior high school students on the topic of Work, Energy, and Simple Machines. The developed devices include Learning Objectives Flow (ATP), teaching modules, PBL–multimodal model designs, and instruments for measuring critical thinking and digital literacy. Validation was conducted by four expert validators using Aiken's V analysis, while reliability was tested with Percentage of Agreement (PA). The research results show that all instruments are in the valid category, with validity values: ATP = 0.82; teaching module = 0.82; PBL-multimodal model = 0.85; critical thinking instrument = 0.84; and digital literacy instrument = 0.84. The reliability of all instruments is also high, namely: ATP = 0.87; teaching module = 0.93; PBL-multimodalal model = 0.91; critical thinking instrument = 0.95; and digital literacy instrument = 0.93. These findings confirm that the developed instrument is content-valid, presentation-valid, construction-valid, and language-valid, and that it is consistent across validators. The validator provided suggestions for improvement, such as variations in creative activities in the ATP, improvements to the teaching modules, multimodal integration in the learning model, condensing critical thinking essay questions, and modifying digital literacy questions into multiple-choice format. Thus, this PBL–multimodal device is proven to be valid and reliable, and has the potential to support 21st-century skills, particularly critical thinking and digital literacy.